Relationship between the talk test and ventilatory threshold - Dehart, Mehgan (My University, 1999)
The Talk Test is a widely recommended form of prescribing exercise intensity, however very few studies have specifically evaluated its physiological validity. This study evaluated the relationship between the Talk Test and physiologic changes occurring with exercise. We examined healthy volunteers during incremental exercise. Each subject (N = 28) completed two maximal exercise tests. One test used gas analysis to identify ventilatory threshold (VT). The second was identical, except without respiratory measurements. During this test, the subject read a standard paragraph and reported whether or not they passed the Talk Test. Outcomes at VT and the last positive, positive/negative, and negative stages of the Talk Test were compared. There was a significant (p < .05) difference between VO2, % VO2peak, HR, and % HRpeak at VT and the positive stage of the Talk Test. There was no significant difference between any of the variables at VT and the positive/negative stage. There was a significant difference between all the outcomes at VT and the negative stage of the Talk Test. We conclude that when subjects could either talk comfortably or were equivocal, they were at or below their VT. Subjects clearly failing the Talk Test were consistently beyond their VT. Thus, the Talk Test is a valid subjective measure to guide exercise prescription.
Keywords: Treadmill exercise tests; Exercise -- Physiological aspects; Respiration -- Measurement; Anaerobiosis